Estudio del comportamiento del consumidor de bebidas alcohólicas de la ciudad de Machala en las edades de 15 a 59 - Espinoza Rojas, Herman Eduardo (2015)
This work is carried out to understand the behavior of consumers of alcoholic beverages and identifying consumer preferences in different aspects such as price, brand, taste, presentation; and offer marketers of alcoholic beverages tools to improve sales and also their income, within the proposed tools for marketers we emphasize the development of a marketing plan where we value 4P considered important within the marketing, strategy aims to increase sales applied to the price, product, place and promotion. For information and develop research proposals raised here the method of inductive deductive research where we start from concrete made to issue our criterion is used, the fact that we are based on the literature review and the survey as the main instrument of research, survey of 400 inhabitants of the city of Machala, the results obtained from this survey allows us to understand what the consumer demands based on the consumption of alcoholic drinks are. Based on these results the proposed implementing tools to improve sales knowing that user requirements part about the brand, the taste of the drink, identifying the places of consumption, on most consumed and what is produced is favorite drink both domestic and imported, the level of preference for high-grade drinks alcohol. With these results we can conclude that in the city of Machala alcohol has a high degree of acceptance by which marketers of alcoholic beverages is recommended to determine the points of supply and put the beer in national brand Pilsener and imported the Corona to get more sales and improve their income